Empirical comparison of deep learning models for fNIRS pain decoding - Fernandez Rojas, Raul; Joseph, Calvin; Bargshady, Ghazal; Ou, Keng-Liang (Frontiers in Neuroinformatics, 2024)
Pain assessment is extremely important in patients unable to communicate and it is often done by clinical judgement. However, this method is complex since observations of patient's behaviour and vital signs might change due to the patient's medical conditions. Therefore, the need for an objective pain assessment method that can assist medical practitioners. Functional near-infrared spectroscopy (fNIRS) has shown promising results to assess the neural function in response of nociception and pain. Previous studies have explored the use of machine learning with hand-crafted features in the assessment of pain. In this study, we aim to expand previous studies by exploring the use of deep learning models (Convolutional Neural Network (CNN), Long Short-Term Memory (LSTM), CNN-LSTM) to automatically extract features from fNIRS data and by comparing these with classical machine learning models using hand-crafted features. The results showed that the deep learning models exhibited favourable results in the identification of different types of pain in our experiment using only fNIRS input data. The combination of CNN and LSTM in a hybrid model (CNN-LSTM) exhibited the highest performance (accuracy = 91.2%) in our problem setting. Statistical analysis using one-way ANOVA with Tukey's (posthoc) test performed on accuracies showed that the deep learning models significantly improved accuracy performance as compared to the baseline models. Overall, deep learning models showed their potential to learn features automatically without relying on manually-extracted features and the CNN-LSTM model could be used as a possible method of assessment of pain in non-verbal patients. Future research is needed to evaluate the generalisation of this method of pain assessment on independent populations and in real-life scenarios.